'But Yehoshuah knew the numbers': Reading Joshua Cohen's Book of Numbers as Biblical Adaptation. Issue 2 (13th September 2017) - Cochran, James M.
This article considers Joshua Cohen's 2015 Book of Numbers as an adaptation of the biblical Numbers. Drawing on personal interviews and Cohen's novel, I trace how Cohen uses the structures and themes of the biblical Numbers to write about the contemporary technological world. By recasting the biblical source into a technological form, Cohen suggests that the digital world offers a kind of freedom, a Promised Land; yet, the freedom of the internet and new technologies is ultimately enslaving, resulting in an alienation of the self. Still, the 2015 Book of Numbers has a hopeful outlook, anticipating the survival of the 'younger generation'.